Adductor longus: An anatomical study to better understand groin pain. Issue 7 (16th April 2022) - Kato, Takuya; Taniguchi, Keigo; Kodesho, Taiki; Nakao, Gakuto; Yokoyama, Yu; Saito, Yuhei; Katayose, Masaki
Abstract: We investigated the shear modulus–passive force relationship in the hip adductor longus (AL) muscles of human cadavers and explored the effect of muscle architecture on the elastic properties of the AL muscle using shear wave elastography (SWE). Nine AL muscles were harvested from a soft, embalmed cadaver. The AL muscles were affixed to a custom‐built device comprising two clamps, a pulley, and a cable to provide passive loads, which were increased from 0 to 600 g in 60‐g increments. The shear modulus of the AL muscle was measured in the proximal (Pro), middle (Mid), and distal (Dis) regions. The masses and anatomical cross‐sectional areas (ACSAs) of the AL muscles were measured. The shear modulus‐passive load relationship of each tested muscle region was analyzed by fitting a least‐squares regression line. Moreover, the rate of increase in the shear modulus per unit load ( s ) was calculated. The shear modulus and passive force were linearly correlated for all AL muscles in each region ( p < 0.01). The mean coefficients of determination ( R 2 ) for Pro, Mid, and Dis were 0.989, 0.986, and 0.982, respectively. The rate of increase in the shear modulus per unit load significantly correlated with the reciprocal of the muscle mass ( r = 0.77, p = 0.02) and ACSA ( r = 0.43, p = 0.03). Shear wave elastography can be used as an indirect measure of passive force in any region of the AL muscle. Additionally, the rate of increase in the shear modulus per unit load could be associated with muscle architectural parameters.